2012
DOI: 10.1128/aem.06192-11
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Lactobacillus rhamnosus GG Pili in Relation to Adhesion and Immunomodulatory Interactions with Intestinal Epithelial Cells

Abstract: Lactobacillus rhamnosus GG, a probiotic with good survival capacity in the human gut, has well-documented adhesion properties and health effects. Recently, spaCBA-encoded pili that bind to human intestinal mucus were identified on its cell surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
304
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(319 citation statements)
references
References 44 publications
12
304
0
3
Order By: Relevance
“…20,21 Nonpilus adhesins of several bacteria also play pivotal roles in adherence to the host and its immune response. In pathogenic bacteria, trimeric autotransporter adhesins 22 and adhesins belonging to a protein family termed microbial surface components recognizing adhesive matrix molecules (MSCRAMMs) 23 were found as virulence factors in Gram-negative and -positive bacteria, respectively.…”
mentioning
confidence: 99%
“…20,21 Nonpilus adhesins of several bacteria also play pivotal roles in adherence to the host and its immune response. In pathogenic bacteria, trimeric autotransporter adhesins 22 and adhesins belonging to a protein family termed microbial surface components recognizing adhesive matrix molecules (MSCRAMMs) 23 were found as virulence factors in Gram-negative and -positive bacteria, respectively.…”
mentioning
confidence: 99%
“…The recent discovery of mucus-binding pili constituted a milestone in understanding how L. rhamnosus strain GG interacts with and signals its host (4,9,21,23). The genetic organization of L. rhamnosus GG pilus cluster is quite similar to some other piliated Gram-positive bacteria, such as E. faecalis (11).…”
Section: Discussionmentioning
confidence: 99%
“…L. rhamnosus GG 2 is globally marketed in probiotic products and has been among the best studied lactic acid bacteria (5)(6)(7)(8). In GG, the discovery that mucus-binding pili signal the intestinal cells has generated new insights into the mechanisms involved in host interactions and underlines the potential contribution of pili in probiotic response (9). However, it is not clear what the signaling mechanisms and molecular components are that are involved in this response.…”
mentioning
confidence: 99%
“…Previous studies have investigated the potential of EPSs as antiproliferative or anticytoxic agents with intestinal epithelial cells (Ruas-Madiedo et al, 2010;Liu et al, 2011), but, the immunomodulatory effects of EPSs on these cells has largely been neglected in the literature. However, Lebeer et al (2012), as part of a much larger investigation, have reported that EPSs isolated from the known probiotic organism Lactobacillus rhamnosus GG had no significant effect on IL-8 mRNA expression in Caco-2 cells. Additionally, a recent review article presented preliminary data in which co-culture with EPS-producing strains of bifidobacteria differentially modulated the secretion of inflammatory cytokines, including IL-8 and IL-6, in the Caco-2 intestinal epithelial cell line (Hidalgo-Cantabrana et al, 2012).…”
Section: Exopolysaccharidesmentioning
confidence: 99%